Virologic and immunologic effects of adding maraviroc to suppressive antiretroviral therapy in individuals with suboptimal CD4+ T-cell recovery. (23rd October 2015) - Cillo, Anthony R.; Hilldorfer, Benedict B.; Lalama, Christina M.; McKinnon, John E.; Coombs, Robert W.; Tenorio, Allan R.; Fox, Lawrence; Gandhi, Rajesh T.; Ribaudo, Heather; Currier, Judith S.; Gulick, Roy M.; Wilkin, Timothy J.; et al.
Abstract : Background: Combination antiretroviral therapy (ART) suppresses HIV-1 replication, but does not restore CD4 + T-cell counts in all individuals. To investigate the effects of maraviroc on HIV-1 persistence and the relations between virologic and immunologic parameters in individuals with incomplete CD4 + T-cell recovery, we performed a prospective, open-label pilot trial in which maraviroc was added to a suppressive ART regimen for 24 weeks. Design: A5256 was a single-arm trial in which individuals on suppressive ART with incomplete CD4 + T-cell recovery added maraviroc for 24 weeks. Methods: We quantified low-level, residual viremia in plasma and total HIV-1 DNA and 2-long terminal repeat (2-LTR) circles in peripheral blood mononuclear cells before and after maraviroc intensification. We also evaluated markers of CD4 + and CD8 + T-cell immune activation (%CD38 + HLA-DR + ) and apoptosis (%caspase3 + /Bcl-2 − ). Results: No effect of maraviroc was found on the probability of detectable plasma viremia (≥1 copy/ml; n = 31, exact McNemar P = 1.0) or detectable 2-LTR circles ( n = 28, P = 0.25) or on total HIV-1 DNA ( n = 28, 90% confidence interval -0.1, +0.3 log10 copies/10 6 CD4 + T-cells). Premaraviroc HIV-1 DNA levels were inversely related to premaraviroc %CD38 + HLA-DR + CD4 + T-cells (Spearman = −0.52, P = 0.004), and lower premaraviroc HIV-1 DNA levels were associated with larger decreases in %CD38 + HLA-DR + CD4 + T-cells during maraviroc intensification (Spearman = 0.44, P = 0.018). Conclusion: In individuals on suppressive ART with incomplete CD4 + T-cell recovery, maraviroc intensification did not affect measures of HIV-1 persistence but did decrease persistent CD4 + T-cell immune activation especially in individuals with low preintensification levels of HIV-1 DNA. Abstract : Supplemental Digital Content is available in the text